A phase II clinical trial of a dental health education program delivered by aboriginal health workers to prevent early childhood caries - Blinkhorn Fiona; Brown Ngiare; Freeman Ruth; Humphris Gerry; Martin Andrew; Blinkhorn Anthony (BMC, 2012)
Abstract Background Early Childhood Caries (ECC) is a widespread problem in Australian Aboriginal communities causing severe pain and sepsis. In addition dental services are difficult to access for many Aboriginal children and trying to obtain care can be stressful for the parents. The control of dental caries has been identified as a key indictor in the reduction of Indigenous disadvantage. Thus, there is a need for new approaches to prevent ECC, which reflect the cultural norms of Aboriginal communities. Methods/Design This is a Phase II single arm trial designed to gather information on the effectiveness of a dental health education program for Aboriginal children aged 6 months, followed over 2 years. The program will deliver advice from Aboriginal Health Workers on tooth brushing, diet and the use of fluoride toothpaste to Aboriginal families. Six waves of data collection will be conducted to enable estimates of change in parental knowledge and their views on the acceptability of the program. The Aboriginal Health Workers will also be interviewed to record their views on the acceptability and program feasibility. Clinical data on the child participants will be recorded when they are 30 months old and compared with a reference population of similar children when the study began. Latent variable modeling will be used to interpret the intervention effects on disease outcome. Discussion The research project will identify barriers to the implementation of a family centered Aboriginal oral health strategy, as well as the development of evidence to assist in the planning of a Phase III cluster randomized study. Trial registration ACTRN12612000712808